A vocational qualifications system fit for adults? Revisiting some ideas from the university for industry. Issue 2 (11th May 2015) - Lester, Stan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to make a case for creating a strand of negotiated qualifications in the English (and more generally UK) vocational education and training (VET) system, using the approach established through Ufi-Learndirect Learning through Work (LtW). Design/methodology/approach – The paper identifies some limitations in the recent Whitehead review of adult vocational education in relation to people already in work. Drawing on research into learning at work, modifications to the VET qualifications system are proposed based on the LtW approach. Findings – The VET qualifications system assumes a purpose of preparing people for occupational entry and developing essential competence. The needs of adults already in work can be accommodated provided that they can be fitted within structures reflecting this assumption. It is less able to meet the bespoke needs of individual workers or employers. The LtW approach, which enables individual accredited programmes to be negotiated, offers a way forward that preserves the integrity of the qualification system. Practical implications – Implementing a LtW-type approach in the VET sector is structurally more difficult than in higher education, although less likely to encounter academic resistance. The main challenge is likely to come from the need to modify regulatory rules and design principles for vocational qualifications. Originality/value – Individually negotiated qualifications have been resisted in VET due to largely unfounded fears about reduced rigour and loss of control of content. The proposed approach offers a means of meeting individual needs while retaining the integrity of the qualifications system and reducing the proliferation of units and content within it.